REGIONAL DEVELOPMENT AND RENEWABLE ENERGY ENTERPRISES. A PORTER’S DIAMOND ANALYSIS - LIARGOVAS, Panagiotis; APOSTOLOPOULOS, Nikos (Theoretical and Practical Research in Economic Fields, 2014)
The purpose of this paper is twofold. On the one hand, it aims to highlight the significant role of regional parameters when analyzing the competitive advantage of renewable energy enterprises in Greece by applying Porter’s diamond model, and at the same time to implement the aforementioned model in the case of solar energy enterprises. The paper suggests that analysis should be spread to lower levels than the national one, because renewable energy production companies, either at the stage of installation or at the stage of operation, are fully affected by local conditions. Measuring or analyzing competiveness of this kind of enterprises is not always easy because there are essential differences in comparison with other types of industrial activity. In this paper, specific regional data are also incorporated in the analysis of the diamond model conditions, which affect competitiveness.